PERAN MEDIASI KEPUASAN KERJA ATAS PENGARUH MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI DAN KINERJA PEGAWAI (Studi pada Pegawai Inspektorat Kota Pasuruan) - Agus Sudarmanto,; Muryati, Muryati; Nasharuddin Mas, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of the ability of work motivation in optimizing employee commitment and performance, either directly or through job satisfaction mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 35 employees of the Pasuruan City Inspectorate. Empirical evidence shows that work motivation is able to optimize employee performance, either directly or through job satisfaction mediation. However, work motivation is not able to optimize organizational commitment, if it is directly related, but if through job satisfaction mediation, this variable is able to increase organizational commitment supported by descriptions of the four variables, all of which are expected, they feel responsible for their responsibilities, are encouraged to develop their potential. , challenging work, superiors praise well, be part of the family, leave the agency, achievement of performance, and based on the main tasks and functions